Designing Emotional and Intuitive Sounds for Tech: Insights From Psychoacoustics - Anjali Bhatara; Xavier Dartis; David Morizet; Sébastien Romagny (Human Behavior and Emerging Technologies)
User interface (UI) sounds communicate information and guide users as they navigate an interface. Research exploring the direct links between these sounds’ physical characteristics and their communicative power is lacking. In the present study, we asked 100 participants to report the emotional and functional connotations of 30 UI sounds from household devices. For each sound, they provided ratings on eight emotion scales and then categorized the sound by its position in time within a user experience (beginning, middle, or end) and by its function (a confirmation, a notification, or a cancelation). We then explored the relation between acoustic characteristics (attack time, release time, spectral centroid height, and mean fundamental frequency) and the effects of the change in perceived pitch and loudness over time (melodic and loudness contour) on participants’ ratings of emotion and categorization of function and time. Results showed effects of the acoustic characteristics, especially release time, as well as effects of melodic and loudness contour on emotion, function, and time in experience. This study provides a basic set of guidelines for intuitive UI sound design and informs the discussion on how sound can be leveraged to enhance tech experiences.